Experimental study on the spectral characteristics and correlation relationship of acoustic emission waveforms before failure of burst prone rock - Wenlong Zhang; Yang Zi; Sitong Xin; Jianju Ren; Yongqian Wang; Bochen Sheng; Guangming Yu (Results in Engineering)
The prevention and control of rock burst disaster has been one of the hot topics in geotechnical engineering disaster research in recent years, and it is also a difficult problem to solve, which has been a key focus of scholars. The occurrence of rock burst is caused by certain media and corresponding mechanical conditions, and has certain precursors. In this study, laboratory experiment was implemented to investigate the stress-strain behavior, failure acoustic emission (AE) signals energy, AE event distribution, waveform frequency spectrum characteristics, waveform fractal representation, etc. of sandstone with burst tendency. The results showed that the linear elastic characteristics of the burst prone rock were obvious, and the damage was instantaneous, sudden, and strong. Some high-energy events occurred shortly after the peak intensity, followed by instantaneous failure. The pre failure AE event was located in a butterfly shape, which was consistent with the results of numerical simulation and theoretical analysis and likely to become a warning sign before the imminent failure. Before the failure occurred, it could not only be judged from the AE energy and positioning form, but also analyzed from the main frequency and corresponding main amplitude. Research has found that the main frequency and corresponding main amplitude also experienced a significant decrease during the failure, and there was a very large consistency in the changes between the two, which shows the fractal representation and has not been found in other studies. The similarity between the main frequency and the main amplitude was not as strong as perceived, but the correlation relationship between the main frequency and the main amplitude was extremely high especially before it was on the brink of failure. The research results can provide reference for the study and judgment of precursors of rock burst, and more importantly, reveals the fractal relationship of AE waveforms.